Temperature distribution of long-length high temperature superconducting cable cooled by slush-nitrogen. (June 2022) - Kim, Bokeum; Kwon, Dohoon; Jeong, Sangkwon
Highlights: A numerical model was established to analyze the pressure and temperature distribution in the HTS cable. The benefit of using slush nitrogen as a coolant was investigated. Using slush nitrogen reduced heat transfer between the cooling channels and further decreased temperature of HTS cable. Abstract: A numerical model is established to calculate the temperature and pressure distributions of the 3 km long high temperature superconducting (HTS) power cable. The model assumes that the configuration of HTS power cable is three phase co-axial shape with counter-flow cooling method. In the numerical model, the circulating nitrogen enters the inner channel of the HTS power cable for cooling at the one end, flows to the other terminal, returns through the outer channel, and exits from the HTS power cable. The numerical model considers the mass, the momentum, and the energy balances of nitrogen, and the heat diffusion inside the HTS layer to obtain the realistic temperature and pressure distributions of the cable. When the long HTS cable is cooled by subcooled liquid nitrogen, the result shows that the maximum temperature of the compact HTS layer cannot be kept under 80 K even though the subcooled liquid nitrogen is supplied at the melting temperature. In order to supply nitrogen with lower enthalpy for ensuring sufficient cooling through the whole cable region, we suggest using slush nitrogen, and analyze it in the detailed numerical model. Thermo-hydraulic equations for slush nitrogen are incorporated in the numerical model. The results show that the maximum temperature of the HTS layer decreases by 6.4 K when slush nitrogen with solid volume fraction of 30% is supplied to the HTS cable. The effect of the inlet enthalpy of nitrogen and the heat transfer characteristics to the temperature distribution is discussed and further elucidated in this paper.